TINJAUAN YURIDIS PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL PADA PENGADILAN NEGERI SEMARANG NOMOR 44/G/2013/PHI.SMG TERHADAP HAK ATASUPAH PROSES PEKERJA YANG DIPUTUS HUBUNGAN KERJA - Regina Reverly; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Process Wages are the fundamental rights of an employee during the period of suspension. This process wages to employees during layoffs. Redundancies occur as a result of the unilateral termination by the employer. As long as the decision is not binding, employees are also still need to get their legislative rights due to this normative rights of workers / laborers can meet their needs. Employee wages received is the source of life. According verdict No. 44 / G / 2013 / PHI / SMG deemed not in compliance with the existing rules, because the court no wage law should be a process plaintiff was dismissed for granted by the completion perselisiham relations. The purpose of this thesis, namely: First, the right to determine to perform the work process relationship (PHK) according to the Law No. 13 2013 Labor, Second, to find out the decision of the Industrial Relations Court analysis in Semarang District Court Number. 44 / G / 2013 / PHI.Smg right to execute the work process, which ends the work relationship.This type of research used in writing this law is a normative legal research. With the method according to the literature data sources, the primary data, secondary data, and tertiary data, data collection techniques in this study by a series of operations of data analysis producing qualitative descriptive data, by studying literature.The study, there are two important things that can be derived. First, wages were the rights of workers under Article 155 Paragraph 2 of Law No. 13 of 2013, which means it is not yet completed for the court decision, the employees / workers and employers be released from his obligations. If the employee does not work prohibited for its obligations by the employer, the employees also have to resort to its right before setting the judgment labor dispute resolution institutions. Second, the Industrial Relations Court Decision No 44 / G / 2013 / PHI.Smg not comply with the principle of legal certainty, justice and the concept of worker. This is due to the lack of thoroughness of judges deciding cases and lack of respect for the rules of due process of the wages of workers / laborers unilaterally terminated the employment provided by the court. Suggestions Author, First, judges must pay attention to the rules in force, even in the case of layoffs, receive particularly regarding the right of workers / workers on the wages of the process. Second, the court must give attention to the rule of law committed as a protection against arbitrary actions by spending other people and pay attention to the rights to be accepted as a form of legal certainty. Keywords: Process Wages- PHK